IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS 4 SEKOLAH DASAR - Sumilat, Margaretha; Tompodung, Pinkan (DIKSAR : Jurnal Pendidikan Dasar, 2023)
This research is research regarding the implementation of the independent curriculum in Indonesian language subjects. The aim of this research is of course to see how the Merdakaa curriculum is implemented in Indonesian language subjects in grade 4 elementary school. In this study, descriptive qualitative research was used and the research subject was the homeroom teacher of class 4. Implementing the independent curriculum, of course by using learning tools that pay attention to CP, TP and ATP, the implementation of the independent curriculum is starting to run well but is not yet optimal if you look at the obstacles and shortcomings. Met by the teacher